Marketing Externalities and Market Development - Emran, M. Shahe; Shilpi. Forhad (World Bank, Washington, D.C., 2013)
The authors use survey data from Bangladesh to present empirical evidence on externalities at household level sales decisions resulting from increasing returns to marketing. The increasing returns that arise from thick market effects and fixed costs imply that a trader is able to offer higher prices to producers if the marketed surplus is higher in villages. The semi-parametric estimates identify highly nonlinear own and cross commodity externality effects in the sale of farm households. The vegetable markets in villages with low marketable surplus seem to be trapped in segmented local market equilibrium. The analysis points to the coordination failure in farm sale decisions as a plausible explanation for the lack of development of rural markets even after market liberalization policies are implemented.